PENGENALAN POLA KEGAGALAN MANAJEMEN PENUNJANG SISTEM PRODUKSI DENGAN TEKNIK CLUSTER - Josowidagdo, Landjono (Industrial and Systems Engineering Assessment Journal (INASEA), 2004)
Implementing pattern recognition techniques into quality of design/manufacturing processes will be guidelines to cover the Management Support System (MSS). All situations normally occurs either in the design phase or proccess analysis such as, engineering and manufacturing reviews. A summary of an engineerâs and teamâs thoughts (including an analysis of items that could go wrong based on experience and past concerns) as a component, subsystem or system is designed to create MSS. This approach will consider the Clustering techniques in the Decision Support Principle Components Analysis (PCA) that parallels the systematic formalizes the management disciplines that an engineer normally goes in any activities or process.